Why Discipline and Happiness Matter in Boosting Government Employee Performance - Sulastri Sulastri; Lindanur Sipatu; Rosida Adam; Arie Kurniawan (Nurul Jadid University, 2025)
This study examines the effect of work discipline and the happiness index on employee performance at the Department of Education, Youth, and Sports of Tojo Una-Una Regency. A quantitative survey method with an associative approach was used, involving 60 proportionally random-selected respondents from a population of 182 employees. Data were analyzed using multiple linear regression with SPSS version 25. The results show that both work discipline and the happiness index simultaneously have a positive and significant effect on employee performance, with an R² value of 0.327. Partially, work discipline (p = 0.025) and the happiness index (p = 0.003) also have a significant effect. These findings indicate that improving employee discipline—such as compliance with working hours and task responsibilities—and enhancing psychological well-being can increase productivity and work effectiveness. The practical implication highlights the importance of human resource management strategies focused on discipline and emotional well-being to improve public sector performance.